ANALISIS PERAN PPATK SEBAGAI SALAH SATU LEMBAGA DALAM MENANGGULANGI MONEY LAUNDERING DI INDONESIA - Toetik Rahayuningsih (Universitas Airlangga, 2013)
The promulgation of the Law No. 8 Year 2010 on the Prevention and Eradication of Money Laundering creates a fundamental advancement of law enforcement in the field of criminal law. The fundamental change includes; broader change of the authority of PPATK to investigate suspicious transactions, blocking delay transaction, recommend surveillance, enforce of administrative sanctions, and conducta joint cooperation on anti money laundering and asset returnsas results of a criminal offence. By the authority PPATKwill be able to maximize its role as focal point in the prevention and eradication of the crime of money laundering and be able to strengthen the cooperation in the event when the suspect rushed out of the country. In the asset recovery program, PPATK plays important role especially in terms of financial information intelligence for the purposes of assets tracing, both on the analysis, and the investigation, prosecution and proceedings in the court.Keywords: authority of PPATK, combating money laundering.